Communities of Security Practices in the Age of Uncertainty - Gheciu, Alexandra (Journal of Regional Security, 2018)
This paper examines some of the challenges involved in recent efforts to create a new community of practice that brings together – within the domain of peacebuilding – NATO and humanitarian actors. In recognition of the need to promote systematic cooperation between the alliance and the humanitarian community, NATO has launched several initiatives aimed at constructing a domain of shared knowledge and common procedures, and, on this basis, cultivating mutual trust and a sense of membership in the same community between representatives of the alliance and members of the NGO community. While these initiatives have enjoyed a certain degree of success, at the deeper level the process of forging a new community of practice among these actors remains challenging and fraught with tension. This process has been rendered particularly complicated by the fact that some of the new initiatives challenge fundamental assumptions about self-identity and purpose both in NATO and within the humanitarian community. Indeed, efforts to construct a new community of practice in the domain of peacebuilding both reflect and contribute to intense debates and contestations within the Atlantic Alliance as well as among NGOs about their evolving identities and, linked to that, appropriate logics of action in the future.